Virtual reality in pediatric emergency department and burn unit: a scoping review of current applications - Ignazio Cammisa; Gemma Eftimiadi; David Korn; Serena Ferretti; Lavinia Capossela; Antonio Gatto; Antonio Chiaretti (Emergency Care Journal)
Virtual reality (VR) represents an innovative and effective tool for reducing pain and anxiety in children undergoing painful procedures in pediatric emergency departments and burn units. VR has the ability to modulate both the sensory and emotional components of pain by immersing children in a virtual world, effectively diverting their attention from the painful experience. Specifically, VR distraction competes for the patient’s attentional resources, reducing their focus on the painful stimulus and, consequently, diminishing the perception of pain. The primary objective of this review was to assess and summarize the current knowledge regarding the use of VR for painful procedures in pediatric emergency and burn units by comparing and analyzing the existing literature. Of the 340 articles reviewed, 25 met the selection criteria and were included in the analysis. These studies examined the use of VR in venous procedures (such as venipuncture, cannulation, and blood sampling) as well as other procedures, including laceration repair and burn wound care. The findings indicated that 20 studies reported a reduction in pain scores, while 9 studies noted a reduction in anxiety scores. Additionally, three studies demonstrated a reduction in procedural time. Overall, the studies supported the efficacy, safety, and feasibility of VR in managing procedural pain and anxiety in pediatric settings. Furthermore, VR use contributed to a reduction in parental and medical stress levels, as well as a decrease in the time spent in the pediatric emergency room. Studies involving larger sample sizes may provide further evidence of VR’s effectiveness across different procedures and age groups.